Immune-based combination therapy for esophageal cancer - Wang, Huiling; Xu, Yufei; Zuo, Fengli; Liu, Junzhi; Yang, Jiqiao (Frontiers in Immunology, 2022)
Esophageal cancer (EC) is an aggressive malignancy raising a healthcare concern worldwide. Standard treatment options include surgical resection, chemotherapy, radiation therapy, and targeted molecular therapy. The five-year survival rate for all stages of EC is approximately 20%, ranging from 5% to 47%, with a high recurrence rate and poor prognosis after treatment. Immunotherapy has shown better efficacy and tolerance than conventional therapies for several malignancies. Immunotherapy of EC, including immune checkpoint inhibitors, cancer vaccines, and adoptive cell therapy, has shown clinical advantages. In particular, monoclonal antibodies against PD-1 have a satisfactory role in combination therapy and are recommended for first- or second-line treatments. Here, we present a systematic summary and analysis of immunotherapy-based combination therapies for EC.